Effectiveness of Cargo Warehouse Use at Soekarno Hatta Airport: Library Research - Agus Suhendra (Dinasti Publisher, 2024)
Abstract: The article on the effectiveness of using cargo warehouses at Soekarno Hatta Airport is a scientific literature review article within the scope of operational management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of operational management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and journals. The findings of this research are as follows: 1) Loading and unloading equipment influences the effectiveness of warehouse use; 2) The frequency of imported commodities influences the effectiveness of warehouse use; 3) International trade influences the effectiveness of warehouse use; and 4) The regulatory system influences the effectiveness of warehouse use.